2021
DOI: 10.3390/nu13103437
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in Celiac Disease: Prevalence, Health Impact, and Clinical Management

Abstract: Iron is an essential nutrient to life and is required for erythropoiesis, oxidative, metabolism, and enzymatic activities. It is a cofactor for mitochondrial respiratory chain enzymes, the citric acid cycle, and DNA synthesis, and it promotes the growth of immune system cells. Thus, iron deficiency (ID) leads to deleterious effects on the overall health of individuals, causing significant morbidity. Iron deficiency anemia (IDA) is the most recognized type of anemia in patients with celiac disease (CD) and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 174 publications
(290 reference statements)
0
12
0
6
Order By: Relevance
“…Several studies have investigated the prevalence of CD in IDA patients, finding variability across time and geographical areas [ 21 ]; however, many of them were biased by the methodologic diagnostic approach used: some studies considered only antibody positivity to CD, reporting a pooled CD prevalence of 1.4%, whereas studies based on biopsy-confirmed CD reported a prevalence of 0.7% [ 22 ]. More relevant data were reported in a metanalysis by Mahadev et al; the authors analyzed 18 studies from several countries (including Italy), reporting a biopsy-confirmed CD prevalence in 3.2% of IDA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the prevalence of CD in IDA patients, finding variability across time and geographical areas [ 21 ]; however, many of them were biased by the methodologic diagnostic approach used: some studies considered only antibody positivity to CD, reporting a pooled CD prevalence of 1.4%, whereas studies based on biopsy-confirmed CD reported a prevalence of 0.7% [ 22 ]. More relevant data were reported in a metanalysis by Mahadev et al; the authors analyzed 18 studies from several countries (including Italy), reporting a biopsy-confirmed CD prevalence in 3.2% of IDA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is probably the most frequent extra-intestinal manifestation of CD [ 23 ]. A recent metanalysis showed that its prevalence varies widely between studies, ranging from 12% to up to 85%, and it is more common in the female sex [ 22 ]. In our study, 54.7% of CD patients were anemic and almost all of them were women (92%, p = 0.0001), confirming the above-reported literature data.…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se de um dos tipos mais comuns de anemia, a qual está intimamente relacionada com o baixo consumo de alimentos ricos em ferro, como carne vermelha, ovo ou espinafres. No entanto, este tipo de anemia também pode surgir após uma hemorragia ou menstruação severa, devido à perda de ferro pelo sangue, ou devido a alguns distúrbios metabólicos, como intolerância ao glúten (Montoro-Huguet et al, 2021).…”
Section: Alimentação Versus Anemia Ferropénicaunclassified
“…Распространенность железодефицитных состояний (ЖДС) среди впервые диагностированных пациентов с целиакией в среднем составляет 12-85%. В свою очередь, частота выявляемости целиакии среди пациентов с анемией -5,5%, причем наиболее часто -среди больных с анемией, рефрактерной к стандартной терапии препаратами железа [6,8,9]. Следует отметить, что ЖДА в 40% случаев -единственное внекишечное клиническое проявление заболевания, следовательно, дети с целиакией относятся к группе риска по развитию ЖДС [1][2][3][4].…”
Section: Introductionunclassified